Peran Kepemimpinan Transformasional Dan Budaya Kerja Terhadap Kinerja Karyawan Pada PT Dinasti Kreatif Indonesia - Fadhil, Muhammad; Imbron Imbron (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to determine the influence of Transformational Leadership and Work Culture on Employee Performance at PT Dinasti Kreatif Indonesia. The research method used is a quantitative approach through the distribution of questionnaires to respondents as the primary data source. The analytical techniques applied include validity testing, reliability testing, multiple linear regression analysis, t-test, F-test, and coefficient of determination (R²). The results show that Transformational Leadership significantly influences Employee Performance, indicated by a t-value of 8.837 with a significance level of 0.000. Work Culture also significantly influences Employee Performance, with a t-value of 6.556 and a significance level of 0.000. Simultaneously, both independent variables have a significant effect on Employee Performance, as shown by an F-value of 58.367 with a significance level of 0.000. The coefficient of determination (R²) of 0.661 indicates that 66.1% of the variation in Employee Performance is explained by these two variables, while the remaining percentage is influenced by other factors outside this study. Thus, this study concludes that the implementation of strong transformational leadership and a positive work culture plays an essential role in improving employee performance. The findings are expected to serve as a reference for companies in developing managerial strategies to create a productive and collaborative work environment.